Is ministers’ use of spin-strategies effective or not? - Knudsen, Søren Bøllingtoft (Politica, 2016)
Hoping to maintain political power, governments rely on their ministers’ ability to play the political game. A key part of this is the blame game in which ministers employ different spin strategies. The question is what strategies they employ and how effective these strategies are? The article compares six Danish ministers’ use of spin strategies based on content coding of 1412 articles from the Danish newspaper Politiken. Generally, the use of spin strategies has not changed significantly over the past 20 years. The most effective way to handle critique is to employ one single spin strategy, the second-best strategy is passivity, and the worst a minister can do to avoid blame is to employ a combination of spin strategies. Finally, quick and slow responses are equally good/bad.